Geoprocessamento aplicado a análise espaço-temporal da Leishmaniose visceral em crianças no Estado do Pará - MELO, Lilia Silvana Cardoso de (2022)
With a wide geographic distribution, Visceral Leishmaniasis is a serious public health problem. Considered as an endemic and epidemic disease, it mainly affects the most needy people, with children being the most affected. The state of Pará has characteristics conducive to the disse-mination of the vector, due to constant social and environmental changes. With this, the work aimed to carry out a space-time analysis of cases of Infantile Visceral Leishmaniasis in the state of Pará, from 2015 to 2019, analyzing the determining factors of the disease, producing a the-matic cartography based on the cases of LVI. For this purpose, data collection was carried out in the Information System of Diseases and Notification (SINAN), provided by the Public Health Department of the State of Pará (SESPA), in addition to the collection of vector data from the area of interest of the Brazilian Institute of Health. of Geography and Statistics (IBGE, 2020). Through the Geographic Information System (GIS), maps were built. To make the location map, the choropleth maps, and spatial autocorrelation of Moran's Local Index relative to pro-pagation and deaths of the disease, the software ArcGis 10.8 was used. The Kernel maps, as well as the map of environmental analysis were worked on the software Qgis 3.16.5 Graphs and tables of the profile of the disease and the climatic patterns were made that contribute to the spread of the pathology. In the period from 2015 to 2019, 2.155 cases of VL were confirmed in Pará, of these 1.170 (54.3%) were children, with greater demand in the mesoregion of Southeast Pará with 14,07 cases per 10 thousand/h inhabitants, with the highest concentration in the municipalities of Eldorado dos Carajás, Canaã dos Carajás, Pau D’Arco and Redenção. The computational techniques from geoprocessing were presented for this study as essential tools, allowing the structuring of a geographic database, for the generation of cartographic pro-ducts, producing information that can help in the urgency of the answers and contribute to the planning and actions of the government. public.